The Negative Impact of Boko Haram Insurgency on Women and Children in Northern Nigeria: An Assessment - Alhaji Ali, Mustapha; Zakuan, Ummu Atiyah Ahmad; Ahmad, Mohammad Zaki bin (American International Journal of Social Science Research, 2018)
This paper studies the negative impacts of Boko Haram insurgency on women and children in northern Nigeria. Indeed, Boko Haram has affected the lives of the general populace in northern Nigeria, precisely women and children, by turning the women to widows and children to orphans, the negative events of the sect groups have continually coursing a serious damage to the lives and properties of the peoples in the northern region. The researcher used the Secondary source in acquiring the appropriate data. The study found that this set of individuals and their negative activities have affected the lives and properties of women and children. It is noted that many women have turned to widows and children to orphans. In view of this, the paper recommends that the government should intervein to provide the affected women and children with some empowerment programmes. It should also provide a good shelter to those that lost their husbands and residents, the government, traditional rulers, and religious leaders should help in assisting the children by enrolling them to schools like their fellow counterparts. There is a need for special rehabilitation and trauma centers in the affected states, especially for women and children who have had terrible knowledge during the insurgency period.